Manifestations of systemic disease in the retina and fundus of cats and dogs - Beckwith-Cohen, Billie; Petersen-Jones, Simon M. (Frontiers in Veterinary Science, 2024)
The fundus is unique in that it is the only part of the body that allows for a noninvasive and uninterrupted view of vasculature and nervous tissue. Utilization of this can be a powerful tool in uncovering salient incidental findings which point to underlying systemic diseases, and for monitoring response to therapy. Retinal venules and arterioles allow the clinician to assess changes in vascular color, diameter, outline, and tortuosity. The retina and optic nerve may exhibit changes associated with increased or decreased thickness, inflammatory infiltrates, hemorrhages, and detachments. While some retinal manifestations of systemic disease may be nonspecific, others are pathognomonic, and may be the presenting sign for a systemic illness. The examination of the fundus is an essential part of the comprehensive physical examination. Systemic diseases which may present with retinal abnormalities include a variety of disease classifications, as represented by the DAMNIT-V acronym, for Degenerative/Developmental, Anomalous, Metabolic, Neoplastic, Nutritional, Inflammatory (Infectious/Immune-mediated/ischemic), Toxic, Traumatic and Vascular. This review details systemic illnesses or syndromes that have been reported to manifest in the fundus of companion animals and discusses key aspects in differentiating their underlying cause. Normal variations in retinal anatomy and morphology are also considered.